Maximum torque-per-amp tracking control of saturated induction motors - Peresada, Sergei; Kovbasa, Serhii; Dymko, Serhii; Bozhko, Sergiy (2017)
An improved maximum torque per Ampere (MTPA) controller for induction motor (IM) drives is presented. The proposed MTPA field oriented controller guarantees asymptotic torque tracking of smooth reference trajectories and maximises the torque per Ampere ratio when the developed torque is constant or slow varying. Due to use closed loop flux observer and high-gain PI controllers for both stator current components the proposed solution provides improved robustness with respect to parameters variations and inverter non-idealities. Experimental tests prove the accuracy of the proposed control over a full torque range. In addition, a higher torque per Ampere ratio is achieved together with an improved efficiency of electromechanical energy conversion.